Governance Constraints and Institutional Dynamics in Road and Bridge Infrastructure Development: Evidence from Kokas District, Indonesia - Saraswaty, Aulia; Attamimi, Aqilah (Pattimura University, 2026)
Infrastructure development plays a critical role in promoting regional connectivity, improving public service delivery, and supporting socio-economic growth, particularly in remote and decentralized regions. However, infrastructure projects in peripheral areas frequently encounter governance-related challenges that constrain their effectiveness and sustainability. This study examines governance challenges in road and bridge infrastructure development in Kokas District, Fakfak Regency, Indonesia, using a public administration perspective. The research focuses on four key governance dimensions: institutional capacity, policy implementation processes, accountability mechanisms, and stakeholder participation. A qualitative case study design was employed to capture contextualized insights into administrative practices and governance dynamics. Data were collected through semi-structured interviews with 15 purposively selected informants, including local government officials, district administrators, project implementers, and community representatives. Document analysis of planning reports, regulatory frameworks, and project records was conducted to triangulate interview findings. Data were analyzed using thematic analysis to identify patterns and relationships across governance dimensions. The findings indicate that governance challenges significantly influence infrastructure development outcomes. Limited institutional capacity, coordination constraints, procedural accountability practices, and predominantly symbolic participation mechanisms collectively shape project implementation processes. These governance conditions contribute to administrative inefficiencies, implementation delays, and reduced infrastructure sustainability. The study highlights that infrastructure development constraints in remote districts are deeply embedded in governance structures rather than technical factors alone. This research contributes to governance and decentralization scholarship by emphasizing the importance of strengthening institutional capacity, coordination mechanisms, transparency practices, and participatory governance to improve infrastructure development effectiveness in decentralized and peripheral contexts.